Scales of justice are out of balance. - GOUTIER, Hegel (1995)
Highlights the persistent prejudice and discrimination faced by women throughout the world. Notes that although health and education for women have advanced by nearly 20 in 20 years, the female working population has increased by only 4. Argues that while laws can be passed to stimulate reforms, only a change in mentality will be effective.